PENGARUH KEPUASAN DAN KEPERCAYAAN PELANGGAN TERHADAP NIAT PEMBELIAN ULANG DI TOKO ONLINE - Ramli Akbar Alamsyah (Manajemen Bisnis, 2016)
The research aims to examine the effect of customer satisfaction and trust on repurchase intention. Sample used 100 respondents taken by purpossive sampling technique of online shoping customer. Path analysis employed to examine the effect customer satisfaction and trust on repurchase intention. the result shows that satisfaction and customer satisfaction have a positive effect on repurchase intention, and trust was mediating the effect of customer satisfaction on repurchase intention.